Sevoflurane induces inflammation of microglia in hippocampus of neonatal rats by inhibiting Wnt/β-Catenin/CaMKIV pathway - Fengjuan Wang; Chuangang Li; Jianhui Shao; Jinfeng Ma (Elsevier, 2021)
Objective: To investigate the effect of sevoflurane on inflammation of microglia in hippocampus of neonatal rats, and to investigate whether the related mechanism is related to Wnt/β-Catenin/CaMKIV pathway. Methods: Neonatal rats were anesthetized with 2% or 3% sevoflurane for 4 h a day for 3 consecutive days. Water maze test was used to detect the effect of sevoflurane anesthesia on memory function of neonatal rats. H&E and Nissl staining were used to observe the pathological damage of hippocampal area of neonatal rats induced by sevoflurane anesthesia. The expression of microglial marker Iba-1 was detected by Immunofluorescence. Immunofluorescence and WB were used to detect the expression CD32b, CD86, TNF-α, IL-6, Wnt3a, β-Catenin and CaMKIV in hippocampus. To further explore the related mechanism, Wnt-3α inhibitor and activator was treated to study the effect of sevoflurane on microglial inflammation in hippocampus of neonatal rats. Results: Sevoflurane anesthesia significantly increased escape latency time, reduced platform crossing times, and damaged the learning and memory ability of neonatal rats. H&E and Nissl staining results showed that sevoflurane anesthesia caused obvious damage to the hippocampus of neonatal rats. Sevoflurane anesthesia promoted the expression of Iba-1 and activated microglia. Sevoflurane anesthesia not only significantly increased the positive expression of CD32b, CD86, TNF-α and IL-6, but also decreased the expression of Wnt3a, β-Catenin and CaMKIV. These results suggested that sevoflurane inhibited Wnt/β-Catenin/CaMKIV pathway. Conclusion: Sevoflurane induces inflammation of microglia in hippocampus of neonatal rats by inhibiting Wnt/β-Catenin/CaMKIV pathway.